Physical education, health and music - Nalundasan-Abijan, Remedios; Claridad-Cruz, Rosario; Miranda, Augusto L.; Isama, Belen G.; Padilla, Angelita C.; Angeles, Aida M. (Manila : St. Augustine Pub, 1997)
Vols. 3 & 4 list as authors : Helen G. Imasa, Angelita C. Padilla, aida M. Angeles.
Includes bibliography.
Keywords: Physical education and training -- Philippines; Health education (Secondary) -- Philippines